Determinants of the Acceptance of Going Concern Audit Opinions - Aldrin Winata; Carmel Meiden; Sugi Suhartono; Yosef Dema; Prima Apriwenni (Budapest International Research and Critics University, 2022)
A going concern audit opinion is an estimate in a firm's financial statements that can be used to determine whether a company is having trouble staying in business. In this study, the research object is a manufacturing business listed on the Indonesia Stock Exchange in the year 2018-2020. The sampling technique was based on the author's criteria and used a purposive sample approach. A total of 117 samples can be obtained as a result of the sample results. This study's findings reveal that audit quality, debt default, and opinion shopping all have a major impact on going-concern audit opinions.